2015
DOI: 10.15866/irecap.v5i1.4824
|View full text |Cite
|
Sign up to set email alerts
|

Medium Frequency Propagation Characteristics of Different Transmission Lines in an Underground Coal Mine

Abstract: A medium frequency (MF) communication system operating in an underground coal mine couples its signals to a long conductor, which acts as an MF transmission line (TL) in a tunnel to permit communications among transceivers along the line. The TL is generally the longest signal path for the system, and its propagation characteristics will have a major impact on the performance of the MF communication system. In this study, the propagation characteristics of three types of MF TLs in two layouts—on the roof and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The measurements showed that the impedances of coal and rock vary not only with frequency but also mine entry location. NIOSH researchers observed impedance differences reaching a factor of 6 between different points of the same entry [2]. Because the impedance measurements directly reflect the electrical properties of the insitu coal and rock, the findings suggest that their electrical properties are dependent on both frequency and location.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The measurements showed that the impedances of coal and rock vary not only with frequency but also mine entry location. NIOSH researchers observed impedance differences reaching a factor of 6 between different points of the same entry [2]. Because the impedance measurements directly reflect the electrical properties of the insitu coal and rock, the findings suggest that their electrical properties are dependent on both frequency and location.…”
Section: Introductionmentioning
confidence: 94%
“…In this TL configuration, the conductor serves as the forward signal path and the surrounding coal and rock serve as the return path. MF propagation parameters have been found to be positiondependent for a TL conductor within an entry [2]. However, the influence of the TL return path on the TL propagation characteristics is still not entirely known because of the complexity in accurately measuring the electrical properties of coal and rock over a long entry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When earth was connected, eight 15-cm-long, 6.3-mm-diameter, stainless steel bolts were attached in parallel using 14-guage wire and stainless steel clips at each end of the TL. Ground connections or electrodes were measured to be less than 50-Ω resistance from 100 to 1000 kHz at both ends of the TL using measurement methods outlined in previous work [14]. …”
Section: Measurementsmentioning
confidence: 99%
“…When the termination at the end of the TL was shorted to ground inside the mine, the end of the TL was attached to eight similar 15-cm stainless steel bolts into the coal rib. Results from tests conducted in this mine show that the impedance achieved from grounding eight bolts does not significantly change when adding more [14]. The results from the coupling measurements are shown in Fig.…”
Section: Measurementsmentioning
confidence: 99%